MAKNA PENDIDIKAN MORAL DALAM PEMBENTUKAN NILAI DAN PERILAKU KEWARGANEGARAAN PADA GENERASI MUDA - Ilvi Nur Dini; Daryono Daryono; Rama Marta Dwi Sanjaya (Jurnal Manajemen Pendidikan, 2026)
Moral education plays a crucial role in shaping the values and civic behavior of young generations amid social dynamics and the challenges of the digital era. This study aims to analyze the meaning of moral education in the formation of values and civic behavior among young people, including their understanding of moral values, the manifestation of these values in civic behavior, and the supporting and inhibiting factors of moral education implementation. This research employs a literature review method with a descriptive qualitative approach. Data were collected from scientific books, national and international journal articles, and relevant academic documents. Data analysis was conducted using content analysis to identify key concepts, findings, and ideas related to moral education and civic education. The findings indicate that young people generally possess a basic understanding of moral values such as honesty, responsibility, discipline, tolerance, and social awareness; however, these values have not been consistently internalized into civic behavior. The manifestation of moral values is reflected in rule compliance, tolerance, and social participation, although gaps remain between moral knowledge and actual practice. Family, school, and community serve as major supporting factors, while negative digital media influences and weak supervision act as significant barriers.